2015
DOI: 10.1097/acm.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Professional Identity and the Formation of Teams in the Veterans Affairs Connecticut Healthcare System’s Center of Excellence in Primary Care Education Program (CoEPCE)

Abstract: This study provides early evidence of successful interprofessional collaboration among NPs and IM residents in a primary care training program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 20 publications
0
22
0
2
Order By: Relevance
“…An inability to support new NPs during transition to demanding practice settings results in turn-over and retention issues for employers (Barnes, 2014). Many NPs consider the level of available support when considering their first job and seek well-established employers with interdisciplinary, patient focused role models for professional socialization (Meyer, Zapatka, & Brienza, 2015).…”
Section: Conceptual and Theoretical Frameworkmentioning
confidence: 99%
“…An inability to support new NPs during transition to demanding practice settings results in turn-over and retention issues for employers (Barnes, 2014). Many NPs consider the level of available support when considering their first job and seek well-established employers with interdisciplinary, patient focused role models for professional socialization (Meyer, Zapatka, & Brienza, 2015).…”
Section: Conceptual and Theoretical Frameworkmentioning
confidence: 99%
“…Early CNP work environment research identified physician relations as the greatest barrier to practice; however, as CNP roles evolve, research findings suggest relationships have improved between CNPs and physician colleagues (Schirle, Norful, et al, 2018), and in some instances, physician colleagues are described as facilitators of CNP practice (Poghosyan et al, 2013). As interactions increase between CNPs and physician colleagues, collaboration, trust and positive attitudes towards one another improve (DiCicco‐Bloom & Cunningham, 2015; Meyer, Zapatka, & Brienza, 2015; Schadewaldt, McInnes, Hiller, & Gardner, 2013). Contrary to CNPs, as the percentage of time CRNAs spend working with anaesthesiologists increases, perceptions of collaborative practice decrease (Taylor, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Organisational‐level recommendations include reducing physical and social barriers between CRNAs and anaesthesiologists, creation of a ‘safe zone’ outside of the clinical area for discussions of ‘legislative efforts’ that impact the respective professions, and group conflict management workshops for nurse anaesthetist students and anaesthesiologist residents during training periods. A recent VA study reported improved collaboration, trust and understanding between CNP students and residents after participation in inter‐professional educational activities during their training period (Meyer et al, 2015), which may be another viable intervention to improve CRNA–anaesthesiologist relations.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: We enjoyed reading the many articles on professional identity formation in the June 2015 issue, [1][2][3][4] and concur that attention to individual professional development is vitally important. We would also like to call attention to the crucial role organizational culture plays in this formation.…”
Section: Cultivating Cultures Of Compassionmentioning
confidence: 99%